Barometer measurements collected during the MARUM Waveglider Adelante mission - Christoph Waldmann; Sebastian Meckel; Andree Behnken; Robert Huber (PANGAEA, 2020)
During the Adelante Mission, Air pressure data near the ocean surface have been collected by utilizing an autonomous surface vehicle, the Wave Glider® SV3 of Liquid Robotics operated by MARUM. The Vaisala PTB 220 sensor had been provided and calibrated by the German Weather Service DWD (Henry Kleta). The real-time data coming from the surface drone were transmitted via an Iridium satellite using the OpenDAM module and subsequently reformatted to be directly fed the data into GTS and PANGAEA.